Microbial Communities in Biocrusts Are Recruited From the Neighboring Sand at Coastal Dunes Along the Baltic Sea - Glaser, Karin; Van, Ahn Tu; Pushkareva, Ekaterina; Barrantes, Israel; Karsten, Ulf (Frontiers in Microbiology, 2022)
Biological soil crusts occur world-wide as pioneer communities stabilizing the soil surface. In coastal primary sand dunes, vascular plants cannot sustain due to scarce nutrients and the low-water holding capacity of the sand sediment. Thus, besides planted dune grass, biocrusts are the only vegetation there. Although biocrusts can reach high coverage rates in coastal sand dunes, studies about their biodiversity are rare. Here we present a comprehensive overview about the biodiversity of microorganisms in such biocrusts and the neighboring sand from sampling sites along the Baltic Sea coast. The biodiversity of bacteria, cyanobacteria, fungi and other microbial eukaryotes were assessed using high throughput sequencing (HTS) with a mixture of universal and group-specific primers. The results showed that the biocrusts recruit their microorganisms mainly from the neighboring sand rather than supporting a universal biocrust microbiome. Although in biocrusts the taxa richness was lower than in sand, 5-times more interactions were identified. This study showed that by comparing neighboring bare surface substrates with biocrusts holds the potential to better understand biocrust development. In addition, the target sequencing approach helps to outline biotic interactions between different microorganisms groups and to identify key players during biocrust development.